Acoustic and pressure characteristics of a ported shroud turbocompressor operating at near surge conditions. (May 2019) - Sharma, S.; Broatch, A.; García-Tíscar, J.; Nickson, A.K.; Allport, J.M.
Abstract: The operation of compressor at lower mass flow rates is limited by surge which is marked by large fluctuations in operational variables and accompanied by significant increase in noise. Ported shroud casing treatment is a widely used method to control the flow near unstable conditions in order to obtain a stable operation and enhance deep surge margin. The research on the acoustic effects of the ported shroud design is limited. Therefore, this paper numerically characterises the acoustic features of a turbocharger compressor with ported shroud design operating at marginal or soft surge conditions and investigates the correlation between acoustic characteristics and the spatial flow structures. The acoustic and the flow field features are analysed using spectral signatures obtained from an experimentally validated numerical model using both performance and acoustic measurements. Propagation of the frequency content through the ducts has been estimated with the aid of the beamforming and method of characteristics to enhance the content coming from the compressor. Expected acoustic phenomena such as rotating order tones and blade passing peaks are correctly identified in the modelled spectrum with the limitation to capture the specific broadband features. Hence, the numerical model can be used to further the research encompassing the impact these flow enhancement solutions have on the noise emission of the turbocharger. Inspection of the flow field shows radially exiting fluid at the ported shroud slot leading to the formation of the high-speed jets exiting the ported shroud cavity. Circumferential propagation of the stall cells is also identified in the impeller. Further inspection of the pressure field through modal decomposition implies the localisation of the energetic noise sources in the impeller downstream components. The influence of the ported shroud cavity on the acoustic characteristic of the compressor is not significant and is limited to the propagation of the tonal noise in the direction of impeller upstream.